Islamic banking in Malaysia: its legal provision and judicial decisions - Md. Dahlan, Nuarrual Hilal; Kamarudin, Abdul Rani (2005)
The practice of Islamic Banking in Malaysia got its first momentum with the establishment of Bank Islam Malaysia Berhad in the early 1980s when the Muslims by and large felt of the need to have an Islamic Bank. By 1990s onward, there were increasing demands for Islamic Banking services and products as the understanding, knowledge and Islamic awareness and renaisance among the Malaysian population increase. In this respect, other conventional banks have also formed their own Islamic Banking Department, providing similar products to meet these demands. This paper will highlight relevant laws in so far as Islamic Banking in Malaysia concerned and attempt to study the case law which have hitherto been decided in Malaysian Courts involving Islamic Banking. Through this paper also legal scenarios and facts on Islamic Banking in Malaysia would be disseminated to others who intend to establish similar establishment and that certain problems could be addressed and certain suggestions could be forwarded to addressed the same.